FDM 3D printing application for making plate pattern on sand casting - Royan, Muhammad; Soemowidagdo, Arianto Leman; Sasongko, Beni Tri; Pradana, Deny Aji (Journal of Engineering and Applied Technology, 2023)
Pattern making in sand casting requires high-level skilled workers since accuracy is the most important concern in producing good quality products. Therefore, conventional pattern-making becomes a major obstacle in developing new products, especially for complicated products as it takes over 70% of the total time in production of the foundry process. This study offers an alternative method in pattern making utilizing 3D technology with the Fuse Deposition Material (FDM) method. It consisted of three steps: planning, production, and evaluation. An intake manifold is an example product that was designed by using Computer Aided Design (CAD) and then imported to a slicer application to obtain the G codes. After the design was printed by using filament of PLA+, it was assembled to create the plate pattern that then was used to produce the intake manifold through casting. The study result shows that the FDM method of the 3D printing technology is feasible for pattern making on sand casting. Deviation and shrinkage of the casting product were still within tolerance. The largest shrinkage is 0.453 mm (1.258%).